SAT0239 PREDICTION OF LONG-TERM EVOLUTIONARY PROFILES IN EOSINOPHILIC GRANULOMATOSIS WITH POLYANGIITIS (CHURG–STRAUSS) BASED ON BASELINE AND FOLLOW-UP CHARACTERISTICS. (June 2019) - Papo, Matthias; Sinico, Renato A.; Teixeira, Vítor; Urban, Maria-Letizia; Mahrhold, Juliane; Monti, Sara; Cassone, Giulia; Schiavon, Franco; Seeliger, Benjamin; Neumann, Thomas; Kroegel, Claus; Groh, Matthieu; et al.
Abstract : Background: Eosinophilic granulomatosis with polyangiitis (EGPA) (Churg–Strauss) is a small-vessel necrotizing vasculitis characterized by blood and tissue eosinophilia and asthma. Glucocorticoids (GCs) control the disease, but GC-dependence is frequent. Evolving concepts distinguish vasculitis-related symptoms from asthma and/or ENT manifestations. That distinction has become even more important since the development of B-cell and eosinophil-targeted therapies. Objectives: This study aimed to describe and identify characteristics predicting long-term EGPA outcomes. Methods: We set up a multicenter European cohort that included 636 EGPA patients. Based on recent consensus, we distinguished 4 EGPA-evolutionary profiles: GC-dependent asthma and/or ENT manifestations (requiring prednisone >7.5 mg/d), ≥1 vasculitis relapse(s) (excluding asthma and/or ENT flares), both phenotypes, and complete remission (no GC-dependent asthma/ENT signs, no vasculitis relapse and prednisone <5 mg/d at last follow-up). Baseline and follow-up characteristics predicting those outcomes were analyzed. Results: After median follow-up of 63 (IQR 30-110) months, 35.8% had GC-dependent asthma and/or ENT manifestations, 12.9% had ≥1 vasculitis relapse(s), 14.3% had both phenotypes, 14.6% were in complete remission, 14.4% were in partial remission and 7.8% had not reach remission. Patients with GC-dependent asthma/ENT manifestations were younger at diagnosis ( p <0.0001), had more frequent GC-treated asthma before overt EGPA ( p =0.002), had more ENT manifestations ( p =0.01) and less frequent MPO-ANCA ( p <0.0001). Their daily GC dose was higher at every time point ( p <0.0001), and they had more frequent active asthma at last follow-up ( p <0.0001). Patients with vasculitis relapse(s) had more frequently neurological manifestations at diagnosis ( p =0.002) and MPO-ANCA positivity ( p <0.0001), and less frequently pulmonary infiltrates ( p =0.031). Median time from diagnosis-to-1 st vasculitis relapse was 25 (11–60) months. During follow-up, their daily GC dose was lower than those with GC-dependent asthma/ENT manifestations, but similar to those in complete remission. At last follow-up, neurological sequelae tended to be more frequent ( p =0.06). Finally, patients in complete remission were older ( p <0.0001), had more fever ( p =0.03), less GC-treated asthma ( p =0.002) and ENT manifestations at diagnosis ( p =0.01), lower daily GC dose during follow-up ( p <0.0001), lower eosinophils count at 6 months ( p =0.002) and less frequent sequelae ( p =0.003). Conclusion: EGPA seems to evolve toward distinct phenotypic profiles, which could be identified using baseline and follow-up characteristics. Early identification of those profiles could allow guided choices of the best therapeutic option. Disclosure of Interests: Matthias Papo: None declared, Renato A. Sinico: None declared, Vítor Teixeira: None declared, Maria-Letizia Urban: None declared, Juliane Mahrhold: None declared, Sara Monti: None declared, Giulia Cassone: None declared, Franco Schiavon: None declared, Benjamin Seeliger: None declared, Thomas Neumann: None declared, Claus Kroegel: None declared, Matthieu Groh: None declared, Chiara Marvisi: None declared, Maxime Samson: None declared, Thomas Barba: None declared, David Jayne Grant/research support from: David Jayne has received research grants from Chemocentryx, GSK, Roche/Genentech and Sanofi-Genzyme. He has received consultancy fees from Astra-Zeneca, Boehringer-Ingelheim, Chemocentryx, Chugai, GSK, Infla-RX, Insmed and Takeda, Bernhard Hellmich Consultant for: Roche, Speakers bureau: Abbvie, MSD, Roche, Novartis, Pfizer, Carlomaurizio Montecucco Speakers bureau: AbbVie, Bristol-Myers Squibb, Celgene, Sanofi, Genzyme, Lilly, MSD, Pfizer, UCB, Carlo Salvarani Grant/research support from: Roche, Consultant for: Eli Lilly and Company, Roche, Abbvie, Jean-Emmanuel Kahn: None declared, Bernard Bonnotte: None declared, Cécile-Audrey Durel: None declared, Luc Mouthon: None declared, Xavier Puéchal: None declared, Loïc Guillevin: None declared, Giacomo Emmi: None declared, Augusto Vaglio: None declared, Benjamin Terrier: None declared